Investigation into the effects of feeding schedule on body condition, aggressiveness, and reproductive failure in group housed sows - J D Schneider; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2006)
A total of 208 sows and 288 gilts (PIC Line C29) were used to determine the influence of feeding frequency (2 versus 6 times per day) in gestation on performance and welfare measurements. The experiment was conducted on a commercial sow farm in northeast Kansas that typically housed gestating sows and gilts in pens. Treatments consisted of feeding similar amounts of feed to each sow or gilt over 2 (07:00 and 15:30) or 6 meals per day (07:00, 07:30, 08:00, 15:30, 16:00, and 16:30 hours). There were 8 sows or 12 gilts in each pen. Gilts and sows were moved to pens after breeding. In gestating sows, there were no differences (P>0.10) between treatments in ADG, backfat change, or variation in body weight. There was a trend (P0.10) among treatments. Sows fed 6 times a day had increased vocalization during the morning (P 0.10) for gilts fed 2 or 6 times per day. Gilts fed twice a day had less weight variation at both d 42 (P0.10) for reproductive performance, skin and vulva lesions, and leg/feet and hoof scores. In conclusion, there were few growth, farrowing, or aggression differences among gilts fed either 2 or 6 times per day. This suggests that either feeding method is suitable for group-housed gilts. Among sows, different feeding frequency resulted in few growth or farrowing-performance differences. Feeding 6 times per day did result in a small, but significant, reduction in skin and vulva lesions and structural-problem scores, while increasing vocalization. Increasing the feeding frequency from 2 to 6 times per day does not seem to have a dramatic negative or positive impact on performance or welfare of group-housed gilts and sows.; Swine Day, 2006, Kansas State University, Manhattan, KS, 2006
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-83-S; Swine day; 2006; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 966; Feeding frequency gilts; Group housing; Gestation; Sows; Swine